Peer Mediation, Emotional Substitution, and the Ambivalence of Care: Informal Care Practices in Indonesian Child Welfare Institutions - Amanda, Violla; Bangsu, Tamrin; Hila, Syahrio Marta (TEMALI : Jurnal Pembangunan Sosial, 2026)
This study examines peer mediation practices carried out by foster older siblings at CWI Aisyiyah Kasih Ibu Bengkulu as a response to the limitations of formal caregiving structures in addressing conflicts among children within an institutional care setting. Drawing on attachment theory, this research critically analyzes how informal caregiving mechanisms operate within the institution and generate ambivalent consequences. Using a qualitative approach and a phenomenological method, the researchers collected data through in-depth interviews with 18 informants (4 foster older siblings, 8 foster children, 1 foster mother, and 5 institutional administrators) and observation. The findings reveal three main results. First, peer mediation functions as a mechanism for restructuring children’s social relations through behavioral modeling and moral guidance, so it not only resolves conflicts but also transforms them into spaces for social learning. Second, the emotional support provided by foster older siblings operates as a substitute attachment system that compensates for the limited emotional capacity within the formal caregiving structure. Third, although peer mediation effectively creates harmony and relational stability, it simultaneously produces ambivalence because it positions foster older siblings in a dual-burden role as both recipients and providers of psychological support. This study affirms that peer mediation within child welfare institutions represents the ambivalence of institutional caregiving in Indonesia: it provides practical solutions to everyday conflicts while simultaneously revealing structural gaps in the distribution of emotional labor and formal caregiving capacity. This study contributes to the development of the sociology of child welfare by offering a critical reading of informal caregiving practices as multidimensional processes layered with power relations and emotional dynamics within the child welfare system.